Does Genotype-Phenotype Correlation Exist in Vitamin D-Dependent Rickets Type IA: Report of 13 New Cases and Review of the Literature - BEREKET, ABDULLAH; ALAVANDA, CEREN; ELTAN, MEHMET; ATA, PINAR; KAYGUSUZ, SARE BETÜL; DEMİRCİOĞLU, SERAP; KIRKGÖZ, TARIK; GÜRAN, TÜLAY (SPRINGER, 2021)
Vitamin D-dependent rickets type IA (VDDR-IA) is caused by biallelic mutations in CYP27B1. Data regarding genotype-phenotype correlation in VDDR-IA are scarce. Here, we aimed to investigate clinical/genotypic features and long-term follow-up of 13 new cases with VDDR-IA and genotype-phenotype correlation of reported cases in the literature. Thirteen patients with VDDR-IA were evaluated. Eight patients had reached their final height at the time of the study and, for whom, long-term outcome data were analyzed. Further, all VDDR-IA patients in the literature (n:183) were analyzed and clinical-genetic features were recorded. The median age of diagnosis was 2.55 +/- 1.13 (1.0-12) years. Initial diagnoses before referral to our clinic were nutritional rickets (n:7), hypophosphatemic rickets (n:2), and pseudohypoparathyroidism (n:1). All had biochemical evidence suggestive of VDDR-IA; except one with elevated 1,25(OH)(2)D3 and another with hyperphosphatemia, in whom pseudohypoparathyroidism was excluded with molecular tests. Combined analyses of our cohort and other series in the literature demonstrated that three most common CYP27B1 mutations are p.F443Pfs*24, c.195 + 2T > G, and p.V88Wfs*71. In Turkish population, p.K192E mutation along with the former two is the most common mutations. Comparison of clinical features demonstrated that c.195 + 2T > G mutation causes the most severe and p.K192E mutation causes the least severe phenotype with respect to age and height at presentation and calcitriol requirement. We found a clear genotype-phenotype correlation in VDDR-IA, notably CYP27B1 intronic c.195 + 2T > G mutation causes a more severe phenotype with lower height SDS at presentation and, higher calcitriol requirement, while less severe phenotype occurs in p.K192E mutation.
Keywords: Rickets; VDDR; 1α -hydroxylase; Hypocalcemia; Hyperphosphatemia; D-DEFICIENCY RICKETS; D-3 1-ALPHA-HYDROXYLASE GENE; ENZYME-ACTIVITY; MUTATIONS; CYP27B1; FAMILY; LEAD